Assessment of the knowledge of people training amateur strength sports about the squat and its variations and the benefits from this fact - Kupczak, Agata; Dolińska, Anna; Zając, Kacper; Suszyński, Krzysztof; Latos, Jan; Górka, Mikołaj; Górka, Dariusz (Journal of Education, Health and Sport, 2023)
Entry The squat pattern is present in the life of every human being from his earliest years. In sports, the squat is one of the most popular exercises, used in almost every discipline in countless variations by both professionals and amateurs. Due to its biomechanics and the degree of involvement of the nervous system and the musculoskeletal system, its use is an essential training link in any plan aimed at developing muscle mass, strength and endurance. The squat pattern is also used in medicine, rehabilitation and improving people suffering from all kinds of injuries and dysfunctions of the locomotor system. Material and methods The study used the diagnostic survey method, with the use of a proprietary questionnaire consisting of 37 questions. The study was conducted among a group of 250 men aged 20-50 practicing amateur strength sports. Conclusions The current state of knowledge about the squat technique (high bar, low bar, front squat) among men practicing strength sports as amateurs is at an insufficient level. Respondents did not show sufficient knowledge about the impact of squats on the human body.